1997
DOI: 10.2307/3579426
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Transforming Growth Factor β and Tumor Necrosis Factor α in the Lungs of Fibrosis-Prone and "Non-Fibrosing" Mice during the Latent Period and Early Phase after Irradiation

Abstract: To evaluate the possibility that TGF-beta and TNF-alpha are involved in fibrosis induced in mouse lung by irradiation, the proportion of cells immunoreactive for each was compared in two strains of mice. C3HeB/FeJ mice develop only classical pneumonitis during the early phase, whereas C57L/J mice develop small, tightly packed areas of inflammation which undergo fibrosis during the latent period, and exhibit progressive fibrosis of large regions of intense inflammation during the early phase. Very few cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
1
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(57 citation statements)
references
References 3 publications
9
44
1
3
Order By: Relevance
“…The polymorphisms at positions ϩ869 and ϩ915, which change codon 10 (T or C, leucine3proline) and codon 25 (G or C, arginine3proline), respectively, are associated with interindividual variation in the levels of TGF-␤ production. This has clinical relevance because several animal and human studies have shown that high TGF-␤ producers develop significantly more lung fibrosis in response to a number of inflammatory triggers such as radiation (31), chemotherapy (32), and lung transplantation (33). For codon 25, the C allele encoding proline for these polymorphisms is associated with lower TGF-␤ synthesis in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphisms at positions ϩ869 and ϩ915, which change codon 10 (T or C, leucine3proline) and codon 25 (G or C, arginine3proline), respectively, are associated with interindividual variation in the levels of TGF-␤ production. This has clinical relevance because several animal and human studies have shown that high TGF-␤ producers develop significantly more lung fibrosis in response to a number of inflammatory triggers such as radiation (31), chemotherapy (32), and lung transplantation (33). For codon 25, the C allele encoding proline for these polymorphisms is associated with lower TGF-␤ synthesis in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Em culturas de fibroblastos e pneumócitos, a irradiação induziu a síntese de TGFβ1 nestas células 36 . Estudos in vivo, em pulmões de camundongos irradiados, mostraram a imunoexpressão da proteína TGFβ1 ativa em fibroblastos próximos à regiões que apresentavam lesões fibróticas 37 e em pneumócitos tipo II 4 . No entanto, estes trabalhos não estudaram especificamente a ativação in situ da proteína TGFβ1 em pulmão.…”
Section: Figura 2 -Medianas Dos Valores Das Contagens De Fibras Colágunclassified
“…Late fibrosis might also develop months to years post-therapy. A possible contribution of cytokines and chemokines to the development of radiation-induced lung injury has been suggested [6][7][8][9][10]. The risk of radiation pneumonitis could also be strongly affected by various endogenous (genotypic) and exogenous (environmental) factors which vary among individuals [11].…”
Section: Introductionmentioning
confidence: 99%